THE IMPLEMENTATION OF STEM EDUCATION IN ENHANCING 21ST-CENTURY SKILLS IN INDONESIA: A LITERATURE REVIEW - Rudi Alviansyah (Integrative Perspectives of Social and Science Journal, 2026)
This study reviews the implementation of STEM education in Indonesia and its contribution to developing students’ 21st-century skills. Using a literature review approach, peer-reviewed national and international articles published between 2019 and 2025 were analyzed, focusing on STEM-based science learning and technology integration. The findings indicate that STEM education positively influences critical thinking, problem-solving, creativity, collaboration, and learning engagement. The integration of educational technologies—particularly Augmented Reality—further supports conceptual understanding and student motivation. Nevertheless, challenges persist regarding teacher readiness, infrastructure disparities, and the dominance of short-term quasi-experimental designs. The study underscores the need for sustained policy support, systematic teacher professional development, and diversified research methodologies to ensure effective and sustainable STEM implementation in Indonesia.